Effect of a Collaborative Palliative Care Intervention vs Usual Care on Quality of Life of Patients with Symptomatic Heart and Lung Diseases: A Randomized Clinical Trial (CO202A) - Bekelman, David; Baron, Anna; Paden, Grady; McBryde, Connor; Welsh, Carolyn; Parsons, Elizabeth; Cheng, Andrew; Turvey, Carolyn; Au, David (Journal of pain and symptom management, 2022)
1. Propose a primary palliative care approach to improve quality of life in chronic obstructive pulmonary disease and chronic heart failure 2. Compare quality of life outcomes from a randomized clinical trial of a primary palliative care intervention Patients with heart failure (HF), chronic obstructive pulmonary disease (COPD), and interstitial lung disease (ILD) endure poor quality of life (QOL) despite conventional therapy. Determine whether a collaborative palliative care intervention improves QOL in outpatients with HF, COPD, or ILD compared to usual care. We conducted a single-blind, 2-arm, multisite randomized clinical trial within 2 VA health care systems. We included outpatients with HF, COPD, and ILD at high risk of hospitalization or death who reported poor QOL. The intervention included symptom care provided by a nurse and psychosocial care provided by a social worker. The nurse and social worker met weekly with a study primary care and palliative care physician, pulmonologist, and cardiologist. The primary outcome was difference in change in QOL from baseline to 6 months between intervention and usual care (FACT-G score, range 0-100, higher score better, clinically meaningful change ∼4-6 points). Analysis used the intent-to-treat approach and mixed models. A total of 306 patients were enrolled (154 intervention, 152 usual care). Participants were generally male (90.2%), White (80.1%), with a mean age of 68.9 (SD 7.7) years; 57.8% had COPD, 21.9% HF, 16% both COPD/HF, 4.2% ILD. Baseline FACT-G scores were similar (intervention, 52.9; usual care, 52.7). FACT-G completion was 76% at 6 months for both intervention and usual care groups. In the intervention arm, 112/154 (73%) patients completed the planned intervention. At 6 months, mean FACT-G score improved by 6.0 points in the intervention arm and 1.4 points in the usual care arm (difference, 4.6; 95% CI 1.8, 7.4; p = 0.001; standardized effect size [ES], 0.41). This effect was observed at all time points (4-month ES 0.30, p = 0.02; 12-month ES 0.36, p = 0.007). A collaborative palliative care intervention demonstrated early, persistent, clinically meaningful improvements in QOL for high-risk outpatients with heart and lung diseases. A team primary palliative care approach increased the reach of palliative care for common, serious noncancer illnesses.